Study of IsCT analogue peptide against Candida albicans and toxicity/teratogenicity in zebrafish embryos (Danio rerio) - Galeane, Mariana C. [UNESP]; Gomes, Paulo C. [UNESP]; Singulani, Junya L. [UNESP]; Mendes-Giannini, Maria J.S. [UNESP]; Fusco-Almeida, Ana M. [UNESP] (Taylor & Francis, 2023)
Aim: An IsCT analogue peptide (PepM3) was designed based on structural studies of wasp mastoparans and tested against Candida albicans. Its effects on fungal cell membranes and toxicity were evaluated. Materials & methods: Antifungal activity was analyzed using a microdilution susceptibility test. Toxicity was assessed using human skin keratinocytes (HaCaT) and zebrafish embryos. Results: PepM3 demonstrated activity against C. albicans and a synergistic effect with amphotericin B. The peptide presented fungicidal action with damage to the fungal cell membrane, low toxicity in HaCat cells and was nonteratogenic in zebrafish embryos. Conclusion: Evaluating structural modifications is essential for the development of new agents with potential activity against fungal pathogens and for the reduction of toxic and teratogenic effects.
Keywords: antifungal peptide; Candida albicans; mass spectrometry; toxicity; zebrafish